Perancangan Sistem Aplikasi Arsip Elektronik Berbasis Website pada Bagian Umum di Kantor DPRD Provinsi Sumatera Selatan - Nyimas Virda Ramadhanty; Yusnizal Firdaus; Esya Alhadi; Mariskha Z (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research was created to design a website-based electronic filing system in the public section of the South Sumatra Province DPRD office. The method used is qualitative analysis in the form of designing a website-based electronic archive storage system in the general section of the South Sumatra Province DPRD office. The archive storage system at the South Sumatra Province DPRD office, especially in the general section, is still manual, namely using a chronological and date system, so that retrieving archives takes a long time, and requires more archive storage space. The design of a website-based electronic archive storage system can make it easier for employees to manage records and does not require a lot of equipment in storage which will take up more space. Finding archives will also be easier and faster because archives are stored electronically.